2019
DOI: 10.29271/jcpsp.2019.02.164
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 Overexpression with Hormone Receptor Status and Triple Negative Breast Carcinoma

Abstract: A total of 91 patients were included with the help of non-probability purposive sampling.All female patients were over 18 years, diagnosed with breast cancer having reports of receptor status confirmed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Our study showed a correlation between HER2 overexpression and tumor grade with a significant p-value similar to Charfi et al [5]. In the present study, the expression of p53 in various grades of urothelial carcinomas was analyzed and it demonstrated a significant association with high tumor grade, which is consistent with the study by Qamar et al [14]. With the above results and observations, this study intended to evaluate the expression of p53, p63, and HER2 in urothelial carcinoma and analyze its association with tumor grade.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed a correlation between HER2 overexpression and tumor grade with a significant p-value similar to Charfi et al [5]. In the present study, the expression of p53 in various grades of urothelial carcinomas was analyzed and it demonstrated a significant association with high tumor grade, which is consistent with the study by Qamar et al [14]. With the above results and observations, this study intended to evaluate the expression of p53, p63, and HER2 in urothelial carcinoma and analyze its association with tumor grade.…”
Section: Discussionsupporting
confidence: 92%
“…Somatic mutations in the TP53 gene occur in almost every type of cancer at rates up to 50% and are more frequent in advanced stage or in cancer subtypes with aggressive behavior (23). In particular, the TP53 gene was found to be mutated in approximately 80% of TNBC, and high levels of p53 in TNBC have been associated with poor prognosis (24).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the receptor may overcome the blockage of the receptor and result in the cell becoming sensitive to hormonal stimulation. Such tendencies are mostly observed in prostate and breast cancers ( 37 – 39 ). The latter is connected with the expression of estrogen receptor which is a predictive and prognostic marker in hormone-dependent cancers.…”
Section: Introductionmentioning
confidence: 95%